2002
DOI: 10.1023/b:glyc.0000014073.23096.3a
|View full text |Cite
|
Sign up to set email alerts
|

Galectin genes: Regulation of expression

Abstract: In this review we have summarized the more recent studies on the expression of mammalian galectins. One interesting observation that can be made is that in most of microarrays and/or differential display analysis performed in recent years one or more galectins have been picked up. From a critical evaluation of the pertinent studies the main conclusion that can be drawn is that, although it is not yet clear whether the 14 galectins identified so far have functions in common, a striking common feature of all gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 69 publications
1
55
0
8
Order By: Relevance
“…[13][14][15] Therefore we hypothesized that DNMTs may be involved in CPT-induced signaling. The time course of DNMT protein levels after CPT treatment is shown in Fig.…”
Section: Confirmation Of Galectin-1 Identificationmentioning
confidence: 99%
“…[13][14][15] Therefore we hypothesized that DNMTs may be involved in CPT-induced signaling. The time course of DNMT protein levels after CPT treatment is shown in Fig.…”
Section: Confirmation Of Galectin-1 Identificationmentioning
confidence: 99%
“…Mammalian galectin-1s are reported to be regulated by various signal pathways (Chiariotti et al, 2002). However, the regulation of fish Pdlgals1 expression has not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the majority of them have a certain structure responsible for recognition, therefore creation of high affinity compounds allows them to be used as vectors for directed drug transport. [11] …”
Section: Application Of Macromolecules With Carbohydrate Residuesmentioning
confidence: 99%